THE KINEMATIC ANALYSIS OF THE GRAB, REAR TRACK AND FRONT TRACK START IN SWIMMING - Bergun Meric Bingul; Cigdem Bulgan; Mensure Aydin; Ozlem Tore (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2015)
The aim of this study was to determine the differences in the kinematic parameters between the grab and track starts (rear-weighted track and front-weighted track). Ten elite male swimmers (mean age± sd 11.3±2.3 years, mean height 152.3±5.6 cm, mean weight 48.2±3.9 kg) participated to this study. Swimmers performed three trials with three different starts technique in indoor pool. Data were recorded directly to the computer by using two basler a602f cameras at 100 hz. and records were analyzed after the test using simi motion 8.5.7 program. The study examined the four kinematic parameters: flight length (FL), flight time (FT) block time (BT), entry time (ET). The kinematic data were compared with friedman test using spss 11.5 program. Based on the comparsion results, it was found statistically significant difference in the parameter FL (p<0.05). Also, the difference between other parameters (FT, ET, BT) is not statistically significant. The flight length during grab start is longer than during front track starts.